Numerical analysis of WaveOne Gold and 2Shape endodontic files during root canal treatment. (March 2022) - Thakur, Vinod Singh; Kankar, Pavan Kumar; Parey, Anand; Jain, Arpit; Kumar Jain, Prashant
This study aims to develop and analyse a finite element model of the endodontic nickel-titanium (NiTi) instrument during the root canal treatment (RCT). The 3D model of the tooth and the endodontic instrument has been created using computer-aided design software. The nonlinear explicit dynamic analysis in the CAE package (ANSYS) has been used to analyse the mechanical behaviour of endodontic instruments such as total deformation, equivalent elastic strain, and equivalent stress during canal preparation. The mechanical behaviour of three commercially available endodontic NiTi alloy instruments such as WaveOne Gold (WOG), 2Shape 1 (TS1) and 2Shape 2 (TS2) endodontic files was evaluated using FEA. Consequently, the effect of deformation, equivalent stress and equivalent elastic strain on endodontic files during cleaning and shaping are investigated and compared. The results show that the total deformation and equivalent elastic strain are maximum in the TS1 endodontic file in comparison to TS2 and WOG files. Graphical abstract